What Research in Science Education is Needed to Strengthen the Elementary-School Science Program? - Mallinson, Jacqueline Buck (Science Education, 1956)
The article reviews the major research findings of recent elementary science studies in the U. S. Several studies have attempted to determine factors such as the scope of elementary science, the topics and principles commonly taught and grade placement of such topics and principles in elementary-school science education. All studies point to the fact that the nature and importance of elementary school science is well established. Another area of elementary science that has been the subject of much research is the methods of enriching the curriculum. It focuses to the effectivity of any teaching device used and the variety of methods applied.